Design and Manufacturing of LPG Gas Leak Detector in The Kitchen - Arif, Muhammad (Kopertis Wilayah X)
How to detect a gas leak is by using an early detection to prevent the occurrence of unwanted conditions. Detector as a gas leak detector can be applied to reduce the incidence of unwanted conditions such as explosion and fire that can result material losses, even death. The most common cause of the leak gas cylinders is corrosion in the gas cylinder, hose and its regulator. However, another cause is forced modification that can create accessories damage such as hose, valve, and regulator. Based on above conditions, additional effort is needed to maintain fire accident due to gas leak from cooking device that uses gas to cook in the kitchen or housing residents. Therefore, there was an action to design a leak gas detector ergonomically, effectively, and efficiently. From its function, detector can react 6 seconds if the position is above of regulator, and 9 seconds if placed on the above of stove at 35 cm distances. After the designed detector is completed and also tested, then detector was able to detect the occurrence of leak gas and it is useful to be used by the public.